PENGARUH PENGEMBALIAN BERBAGAI BIOMASSA TANAMAN TERHADAP SERANGAN HAMA PENGGEREK BATANG KEDELAI Agromyza sojae Zehntn - I. Baidowi; J. Tethool; H S. Pribadi (Universitas Tribhuwana Tunggadewi, 2012)
Afield experiment was conducted at Kampung Desay, District of Manokwari to determine the effect of several biomass applied to soil on the development of soybean stem borer infestations. A completely randomized block design was used with three replications. Seven treatments consisting of biomass monoculture of maize, peanut, soybean, mungbean and biomass intercropping maize + peanut, maize + soybean, maize + mungbean were tested. The results showed that biomass monoculture of maize significantly reduced intensity and population of stem borer. There was no significant different among production components, but the highest biomass was observed for intercropping maize + mungbean